Przekład i oryginał. Polska i francuska wersja osiemnastowiecznego dzieła apologetycznego - Partyka, Joanna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
The author juxtaposes the little-known dialogue treatise of Jakub Zajączkowski’s Rozmowy filozoficzne (Philosophical Conversations, 1780) with its French prototype, Observations philosophiques (1771) by François Xavier de Feller. The works refer to the Pre-Enlightenment and Enlightenment philosophical and theological discussions in which issues in the field of natural science, geology, astronomy, and physics arise. The comparison yields some interesting conclusions.